Aesthetic in Puppet Performance: Lakon Lahire Gatotkaca - Fadri, Zainal (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2021)
Puppet show is still an entertainment that is full of values and meaning in some Javanese people. The existence of puppets on the Java’s island is caused by the spread of puppets in Java when the Sunan Kalijaga era spread Islam. Puppet shows save the values and rules of life inherent in the conditions of society. Values of life are conveyed by portraying puppet plays and slipping a few jokes as entertainment in the show. This research is a library research and supported by direct observation watching puppet shows. The author analyzes the aesthetic dimenasi contained in a puppet show. The results of this study are some of the aesthetic values contained in the puppet play Lahire Gatotkaca. The aesthetics contained in the puppet show are the value of the text beauty, the value of the show beauty and the norms that are conveyed in a relaxed and light manner.